Pengaruh Kualitas Produk, Harga, dan Brand Image Terhadap Keputusan Pembelian Produk Pada Pt. Original Nest Indonesia - Siburian, Claudia Patricia; Tanjung, Yahya (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the influence of product quality, price, and brand image on purchasing decisions at PT. Original Nest Indonesia using Partial Least Squares (PLS) analysis. The results indicate that, partially, product quality has a positive and significant effect on purchasing decisions. Similarly, price and brand image also show positive and significant effects on purchasing decisions. Simultaneously, the findings reveal that product quality, price, and brand image collectively influence consumer purchasing decisions. Therefore, it can be concluded that the research model, which incorporates product quality, price, and brand image as independent variables, is able to explain a significant portion of the variation in purchasing decisions. However, to enhance the effectiveness of marketing strategies, the company is encouraged to explore additional factors beyond this model—such as customer experience, digital promotion strategies, and social environmental influences—that may also affect consumer decision-making